Consultation clinics for complementary and alternative medicine at Japanese university hospitals: An analysis at Tokushima University Hospital - YANAGAWA, HIROAKI (D.A. Spandidos, 2010)
Here, we report on a Consultation Clinic for Complementary and Alternative Medicine (CAM) which we established at Tokushima University Hospital in July of 2007 with the aim of providing person-to-person information on CAM, though not CAM therapy itself. In December of 2008, we received 55 applications for consultation, 37% concerning health foods, 37% Japanese herbal medicine (Kampo), and 26% various other topics. The consultants (nutritionists and pharmacists) communicated individually with 38 applicants; malignancies (26%) and cardiovascular disease (24%) were the main underlying concerns. To promote the quality of consultation, data was collected by means of focus group interviews concerning the perspective of the consultants. Safe and effective use of CAM requires a network of communication linking individuals, consultation teams, physicians, primary care institutions and university hospitals. To advance this goal, we plan to broaden the efforts described herein. Our findings indicate that the specific role of the consultation clinic in promoting the scientific use of CAM merits further study.